2002
DOI: 10.4049/jimmunol.168.6.2745
|View full text |Cite
|
Sign up to set email alerts
|

Focal Localization of Placental Protein 14 Toward Sites of TCR Engagement

Abstract: TCR signal transduction is amplified by the dynamic accumulation of accessory molecules at APC-T cell contact sites, along with the simultaneous exclusion from these sites of negative regulators, such as certain tyrosine phosphatases and large glycosylated proteins. However, given the general nature of the cytoskeleton-driven clustering mechanism underlying molecular segregation events at the APC-T cell interaction site, the possibility exists that negative regulators might similarly be segregated at these sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…We have reported that PP14 directly inhibits human T cells and accounts for the T cell inhibitory activity of AF (37). Our findings further suggested that PP14 targets early events during TCR signal transduction (37), facilitates the dephosphorylation of TCR-induced phosphoproteins, (38), and has the intriguing capacity to elevate TCR activation thresholds (39). This latter finding points to an unusual immunoregulatory mechanism for PP14 that is dis-tinct from that of other better characterized T cell suppressive factors (such as cyclosporin A).…”
supporting
confidence: 66%
“…We have reported that PP14 directly inhibits human T cells and accounts for the T cell inhibitory activity of AF (37). Our findings further suggested that PP14 targets early events during TCR signal transduction (37), facilitates the dephosphorylation of TCR-induced phosphoproteins, (38), and has the intriguing capacity to elevate TCR activation thresholds (39). This latter finding points to an unusual immunoregulatory mechanism for PP14 that is dis-tinct from that of other better characterized T cell suppressive factors (such as cyclosporin A).…”
supporting
confidence: 66%
“…In this way, PP14 has opposite effects to costimulation through CD28 (37). Other mechanistic clues lie in the dependence of the T cell inhibitory activity of PP14 on the surface phosphatase CD45 (7), suggesting that PP14 may somehow interfere with the transit of CD45 and perhaps other components in and out of APC:T cell contact sites (5).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the amplifying effects of costimulation, we have previously demonstrated that the immunomodulatory glycoprotein, placental protein 14 (PP14; 3 also known as glycodelin (4)), translocates to APC:T cell contact sites, where it decreases stability of TCR-induced phosphoproteins (5). This latter activity of PP14 fits in well with the antagonism between CD28-mediated costimulation and PP14-mediated inhibition (6) as well as with recent data indicating that the inhibitory activity of PP14 is mediated by the tyrosine phosphatase receptor, CD45 (7).…”
Section: N Aive Cd4mentioning
confidence: 99%
See 2 more Smart Citations